Social'no-psichologiceskie sostavljajušcie funkcional'nogo imidža trenera po futbolu - Petrovskaja, T.; Malinovskii, A. (Science in Olympic Sport, 2017)
The article presents a theoretical analysis of the issue of the coach's image and its impact on the sports performance along with the theoretical justification and empirical substantiation of social and psychological components of the image of a sports coach. Individual psychological characteristics that determine the formation of the image of a successful football coach were identified. The results of our own empirical studies using SPSS software allowed us to determine the factors and individual psychological characteristics forming the image of a successful football coach. The identified components that determine the formation of an effective professional image of a football coach can be taken into account in the process of forming and correcting the image at different stages of professional development.